2021
DOI: 10.1108/ijpsm-03-2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration among public organizations: a systematic literature review on determinants of interinstitutional performance

Abstract: PurposeThe concept of collaboration has received increased attention from scholars in public management, as it has been seen as a viable solution to address “wicked” problems. Solving such problems may require a horizontal collaboration within the same governmental jurisdiction or, vertically, between different levels of government. Despite broad interest from the field of public management, the dynamics of public interinstitutional collaboration have received little attention within the literature. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 115 publications
(275 reference statements)
0
26
0
Order By: Relevance
“…The findings of this review that facilitation and leadership are critical to success, are consistent with earlier reviews. Costumato [ 55 ] found that power sharing, trust, leadership style and formalisation can increase the effectiveness of public interagency collaboration. Brush et al [ 56 ] found that member diversity, power sharing, decision making, engagement, trust, conflict resolution, fair allocation of resources, and moving research into systems and policy change are critical success factors in community research partnerships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this review that facilitation and leadership are critical to success, are consistent with earlier reviews. Costumato [ 55 ] found that power sharing, trust, leadership style and formalisation can increase the effectiveness of public interagency collaboration. Brush et al [ 56 ] found that member diversity, power sharing, decision making, engagement, trust, conflict resolution, fair allocation of resources, and moving research into systems and policy change are critical success factors in community research partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…This review included a range of interventions using systems theory, which has been absent in previous reviews [ 6 ]. The diversity of theoretical frameworks and settings in the included studies improves generalisability of results, as other notable reviews focus on one particular methodology such as CBPR [ 56 ], or setting such as the public service [ 55 ] or research [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas collaboration is a fluid mechanism, 28 (intersectoral) policy and governance appear to be entities/issues with a degree of stability. Intersectoral health policy is equivalent to HiAP, defined as ‘an approach to public policies across sectors that systematically takes into account the health implications of decisions, seeks synergies and avoids harmful health impacts in order to improve population health and health equity.…”
Section: Intersectoral Policy and Governancementioning
confidence: 99%
“…Research on innovation in public administration and management has provided crucial knowledge about the barriers and drivers of innovation (Cinar et al , 2019; Thøgersen et al , 2021; Walker, 2014), about innovation in governance (Moore and Hartley, 2008; Sørensen and Torfing, 2019; Costumato, 2021) and about the role of top-level managers (Ricard et al , 2017). However, findings suggest that the development of public policy is often decoupled from its implementation (Pihl-Thingvad and Klausen, 2020) and that top-down strategies should be combined with other, locally embedded strategies (Ryan et al , 2008).…”
Section: Managing Public Innovationmentioning
confidence: 99%